The Role of Depression, Anxiety, and Stress in Problematic Smartphone Use among a Large Sample of Iranian Population - Razieh Pourafshari; Tara Rezapour; Parnian Rafei; Javad Hatami (Journal of Affective Disorders Reports, 2022)
Background: Smartphones have greatly facilitated today's human life. However, problematic smartphone use (PSU) could negatively impact mental health. Findings from studies of people in Western countries and Eastern Asia have indicated that individuals with psychopathological symptoms of depression, anxiety, and stress are more likely to use smartphones problematically. Aim: This study investigated whether depression, anxiety, and stress were associated with PSU among the Iranian population. Methods: This cross-sectional study was conducted in 2020 using a web-based questionnaire promoted through social media. All participants (n = 2569) completed the Smartphone Addiction Scale (SAS) as well as the Depression, Anxiety, and Stress Scale-21 Items (DASS-21). A linear multivariate regression model was created to investigate the role of psychopathological symptoms of depression, anxiety, and stress in PSU. Results: We found that for every one-unit increase in subscales of stress, depression and anxiety, the SAS scores increased by β1 = 0.24 (95%CI: [0.18, 0.29]), β2 = 0.13 (95%CI: [0.09, 0.18]), and β3 = 0.14 (95% CI: [0.09, 0.18]), respectively. Significant correlations were also found between depression (r = 0.38, p < 0.01), anxiety (r = 0.36, p < 0.01) and stress (r = 0.42, p <0.01) subscales of DASS-21 and PSU. Conclusions: Our findings suggest that general depression, anxiety, and stress symptoms in daily life might lead to problematic use of smartphones among the Iranian population.